Leaf phosphorus allocation and photosynthesis in native Australian plants differs between soil parent material types - Kazi R. Mehnaz; Erin I. E. Rogers; David S. Ellsworth (Plant and Soil, 2026)
Background and aims There is considerable interest in how plants allocate phosphorus (P) and how this varies by environment. How leaf P fractions change with soil P supplies and soil type is essential to understand the roles of P in storage, structure and biochemistry including photosynthesis. Here, we contrasted the P allocation patterns for native woody plants in south-eastern Australia on soils derived from either P-poor sedimentary or P-rich igneous parent materials. Methods We measured total leaf P and four leaf P fractions: inorganic phosphate (P i ), metabolite P, nucleic acid P, and lipid P for 33 native species. We also measured photosynthetic capacity ( A sat ) for species across four sites with contrasting soil P and parent material types: high total soil P from basalt versus low total soil P in sands. Results The leaf P i fraction scaled consistently with total leaf P within and across the high-P versus low-P sites. Species growing on high P soils from basalt tended to have similar P fractions of total P to those of species on low P soils, except for the lipid P fraction which was greater for species at high P sites. There was a substantial reduction in P allocated to the lipid fraction for species on low P soils, especially in Proteaceae species. Leaf photosynthetic P-use efficiency was significantly higher with lower leaf P concentration. Conclusion The adaptive strategy of reducing phospholipids in leaves occurs in multiple species in low-P environments, including non-Proteaceae. This resulted in species from more than one plant family maintaining lower leaf P concentrations on sedimentary-derived soils than on igneous soils, thus achieving more efficient P use in photosynthesis at low P.

Understanding urban tree heat and drought stress by tracking growth and recovery following an extreme year - Renée M. Marchin; Manuel Esperon-Rodriguez; Mark G. Tjoelker; David S. Ellsworth (Landscape and Urban Planning, 2025)

Metformin treatment of juvenile mice alters aging-related developmental and metabolic phenotypes in sex-dependent and sex-independent manners - Yun Zhu; Morgan Engmann; David Medina; Xiuqi Han; Pratyusa Das; Andrzej Bartke; Buffy S. Ellsworth; Rong Yuan (GeroScience, 2024)

Decoupling between stomatal conductance and photosynthesis occurs under extreme heat in broadleaf tree species regardless of water access - Renée M. Marchin; Belinda E. Medlyn; Mark G. Tjoelker; David S. Ellsworth (Global Change Biology, 2023)
High air temperatures increase atmospheric vapor pressure deficit (VPD) and the severity of drought, threatening forests worldwide. Plants regulate stomata to maximize carbon gain and minimize water loss, resulting in a close coupling between net photosynthesis ( A net ) and stomatal conductance ( g s ). However, evidence for decoupling of g s from A net under extreme heat has been found. Such a response both enhances survival of leaves during heat events but also quickly depletes available water. To understand the prevalence and significance of this decoupling, we measured leaf gas exchange in 26 tree and shrub species growing in the glasshouse or at an urban site in Sydney, Australia on hot days (maximum T air > 40°C). We hypothesized that on hot days plants with ample water access would exhibit reduced A net and use transpirational cooling leading to stomatal decoupling, whereas plants with limited water access would rely on other mechanisms to avoid lethal temperatures. Instead, evidence for stomatal decoupling was found regardless of plant water access. Transpiration of well‐watered plants was 23% higher than model predictions during heatwaves, which effectively cooled leaves below air temperature. For hotter, droughted plants, the increase in transpiration during heatwaves was even more pronounced— g s was 77% higher than model predictions. Stomatal decoupling was found for most broadleaf evergreen and broadleaf deciduous species at the urban site, including some wilted trees with limited water access. Decoupling may simply be a passive consequence of the physical effects of high temperature on plant leaves through increased cuticular conductance of water vapor, or stomatal decoupling may be an adaptive response that is actively regulated by stomatal opening under high temperatures. This temperature response is not yet included in any land surface model, suggesting that model predictions of evapotranspiration may be underpredicted at high temperature and high VPD.

Discovery and exploration of monosaccharide linked dimers of galectin-3 inhibitors to target fibrosis - Jacob J. Swidorski; Brett R. Beno; Chunjian Liu; David S. Yoon; Kaushik Ghosh; Harinath Sale; Devang Shah; Kriti Acharya; Joseph Yanchunas; Priyanka Haldar; Narasimharaju Kalidindi; Jinal K. Shukla; et al. (Medicinal Chemistry Research, 2023)

Extreme heat increases stomatal conductance and drought‐induced mortality risk in vulnerable plant species - Renée M. Marchin; Diana Backes; Alessandro Ossola; Michelle R. Leishman; Mark G. Tjoelker; David S. Ellsworth (Global Change Biology, 2022)
Tree mortality during global‐change‐type drought is usually attributed to xylem dysfunction, but as climate change increases the frequency of extreme heat events, it is necessary to better understand the interactive role of heat stress. We hypothesized that some drought‐stressed plants paradoxically open stomata in heatwaves to prevent leaves from critically overheating. We experimentally imposed heat (>40°C) and drought stress onto 20 broadleaf evergreen tree/shrub species in a glasshouse study. Most well‐watered plants avoided lethal overheating, but drought exacerbated thermal damage during heatwaves. Thermal safety margins (TSM) quantifying the difference between leaf surface temperature and leaf critical temperature, where photosynthesis is disrupted, identified species vulnerability to heatwaves. Several mechanisms contributed to high heat tolerance and avoidance of damaging leaf temperatures—small leaf size, low leaf osmotic potential, high leaf mass per area (i.e., thick, dense leaves), high transpirational capacity, and access to water. Water‐stressed plants had smaller TSM, greater crown dieback, and a fundamentally different stomatal heatwave response relative to well‐watered plants. On average, well‐watered plants closed stomata and decreased stomatal conductance ( g s ) during the heatwave, but droughted plants did not. Plant species with low g s , either due to isohydric stomatal behavior under water deficit or inherently low transpirational capacity, opened stomata and increased g s under high temperatures. The current paradigm maintains that stomata close before hydraulic thresholds are surpassed, but our results suggest that isohydric species may dramatically increase g s (over sixfold increases) even past their leaf turgor loss point. By actively increasing water loss at high temperatures, plants can be driven toward mortality thresholds more rapidly than has been previously recognized. The inclusion of TSM and responses to heat stress could improve our ability to predict the vulnerability of different tree species to future droughts.

Increasing aridity will not offset CO 2 fertilization in fast‐growing eucalypts with access to deep soil water - Daniel Nadal‐Sala; Belinda E. Medlyn; Nadine K. Ruehr; Craig V. M. Barton; David S. Ellsworth; Carles Gracia; David T. Tissue; Mark G. Tjoelker; Santi Sabaté (Global Change Biology, 2021)
Rising atmospheric [CO 2 ] ( C a ) generally enhances tree growth if nutrients are not limiting. However, reduced water availability and elevated evaporative demand may offset such fertilization. Trees with access to deep soil water may be able to mitigate such stresses and respond more positively to C a . Here, we sought to evaluate how increased vapor pressure deficit and reduced precipitation are likely to modify the impact of elevated C a (e C a ) on tree productivity in an Australian Eucalyptus saligna Sm. plantation with access to deep soil water. We parameterized a forest growth simulation model (GOTILWA+) using data from two field experiments on E. saligna : a 2‐year whole‐tree chamber experiment with factorial C a (ambient =380, elevated =620 μmol mol −1 ) and watering treatments, and a 10‐year stand‐scale irrigation experiment. Model evaluation showed that GOTILWA+ can capture the responses of canopy C uptake to (1) rising vapor pressure deficit ( D ) under both C a treatments; (2) alterations in tree water uptake from shallow and deep soil layers during soil dry‐down; and (3) the impact of irrigation on tree growth. Simulations suggest that increasing C a up to 700 μmol mol −1 alone would result in a 33% increase in annual gross primary production (GPP) and a 62% increase in biomass over 10 years. However, a combined 48% increase in D and a 20% reduction in precipitation would halve these values. Our simulations identify high D conditions as a key limiting factor for GPP. They also suggest that rising C a will compensate for increasing aridity limitations in E. saligna trees with access to deep soil water under non‐nutrient limiting conditions, thereby reducing the negative impacts of global warming upon this eucalypt species. Simulation models not accounting for water sources available to deep‐rooting trees are likely to overestimate aridity impacts on forest productivity and C stocks.

Low phosphorus supply constrains plant responses to elevated CO 2 : A meta‐analysis - Mingkai Jiang; Silvia Caldararu; Haiyang Zhang; Katrin Fleischer; Kristine Y. Crous; Jinyan Yang; Martin G. De Kauwe; David S. Ellsworth; Peter B. Reich; David T. Tissue; Sönke Zaehle; Belinda E. Medlyn (Global Change Biology, 2020)
Phosphorus (P) is an essential macro‐nutrient required for plant metabolism and growth. Low P availability could potentially limit plant responses to elevated carbon dioxide (eCO 2 ), but consensus has yet to be reached on the extent of this limitation. Here, based on data from experiments that manipulated both CO 2 and P for young individuals of woody and non‐woody species, we present a meta‐analysis of P limitation impacts on plant growth, physiological, and morphological response to eCO 2 . We show that low P availability attenuated plant photosynthetic response to eCO 2 by approximately one‐quarter, leading to a reduced, but still positive photosynthetic response to eCO 2 compared to those under high P availability. Furthermore, low P limited plant aboveground, belowground, and total biomass responses to eCO 2 , by 14.7%, 14.3%, and 12.4%, respectively, equivalent to an approximate halving of the eCO 2 responses observed under high P availability. In comparison, low P availability did not significantly alter the eCO 2 ‐induced changes in plant tissue nutrient concentration, suggesting tissue nutrient flexibility is an important mechanism allowing biomass response to eCO 2 under low P availability. Low P significantly reduced the eCO 2 ‐induced increase in leaf area by 14.3%, mirroring the aboveground biomass response, but low P did not affect the eCO 2 ‐induced increase in root length. Woody plants exhibited stronger attenuation effect of low P on aboveground biomass response to eCO 2 than non‐woody plants, while plants with different mycorrhizal associations showed similar responses to low P and eCO 2 interaction. This meta‐analysis highlights crucial data gaps in capturing plant responses to eCO 2 and low P availability. Field‐based experiments with longer‐term exposure of both CO 2 and P manipulations are critically needed to provide ecosystem‐scale understanding. Taken together, our results provide a quantitative baseline to constrain model‐based hypotheses of plant responses to eCO 2 under P limitation, thereby improving projections of future global change impacts.

Global response patterns of plant photosynthesis to nitrogen addition: A meta‐analysis - Xingyun Liang; Tong Zhang; Xiankai Lu; David S. Ellsworth; Hormoz BassiriRad; Chengming You; Dong Wang; Pengcheng He; Qi Deng; Hui Liu; Jiangming Mo; Qing Ye (Global Change Biology, 2020)
A mechanistic understanding of plant photosynthetic response is needed to reliably predict changes in terrestrial carbon (C) gain under conditions of chronically elevated atmospheric nitrogen (N) deposition. Here, using 2,683 observations from 240 journal articles, we conducted a global meta‐analysis to reveal effects of N addition on 14 photosynthesis‐related traits and affecting moderators. We found that across 320 terrestrial plant species, leaf N was enhanced comparably on mass basis ( N mass , +18.4%) and area basis ( N area , +14.3%), with no changes in specific leaf area or leaf mass per area. Total leaf area (TLA) was increased significantly, as indicated by the increases in total leaf biomass (+46.5%), leaf area per plant (+29.7%), and leaf area index (LAI, +24.4%). To a lesser extent than for TLA, N addition significantly enhanced leaf photosynthetic rate per area ( A area , +12.6%), stomatal conductance ( g s , +7.5%), and transpiration rate ( E , +10.5%). The responses of A area were positively related with that of g s , with no changes in instantaneous water‐use efficiency and only slight increases in long‐term water‐use efficiency (+2.5%) inferred from 13 C composition. The responses of traits depended on biological, experimental, and environmental moderators. As experimental duration and N load increased, the responses of LAI and A area diminished while that of E increased significantly. The observed patterns of increases in both TLA and E indicate that N deposition will increase the amount of water used by plants. Taken together, N deposition will enhance gross photosynthetic C gain of the terrestrial plants while increasing their water loss to the atmosphere, but the effects on C gain might diminish over time and that on plant water use would be amplified if N deposition persists.

Growing‐season temperature and precipitation are independent drivers of global variation in xylem hydraulic conductivity - Pengcheng He; Sean M. Gleason; Ian J. Wright; Ensheng Weng; Hui Liu; Shidan Zhu; Mingzhen Lu; Qi Luo; Ronghua Li; Guilin Wu; Enrong Yan; Yanjun Song; et al. (Global Change Biology, 2020)
Stem xylem‐specific hydraulic conductivity ( K S ) represents the potential for plant water transport normalized by xylem cross section, length, and driving force. Variation in K S has implications for plant transpiration and photosynthesis, growth and survival, and also the geographic distribution of species. Clarifying the global‐scale patterns of K S and its major drivers is needed to achieve a better understanding of how plants adapt to different environmental conditions, particularly under climate change scenarios. Here, we compiled a xylem hydraulics dataset with 1,186 species‐at‐site combinations (975 woody species representing 146 families, from 199 sites worldwide), and investigated how K S varied with climatic variables, plant functional types, and biomes. Growing‐season temperature and growing‐season precipitation drove global variation in K S independently. Both the mean and the variation in K S were highest in the warm and wet tropical regions, and lower in cold and dry regions, such as tundra and desert biomes. Our results suggest that future warming and redistribution of seasonal precipitation may have a significant impact on species functional diversity, and is likely to be particularly important in regions becoming warmer or drier, such as high latitudes. This highlights an important role for K S in predicting shifts in community composition in the face of climate change.

Lower photorespiration in elevated CO 2 reduces leaf N concentrations in mature Eucalyptus trees in the field - Agnieszka Wujeska‐Klause; Kristine Y. Crous; Oula Ghannoum; David S. Ellsworth (Global Change Biology, 2019)
Rising atmospheric CO 2 concentrations is expected to stimulate photosynthesis and carbohydrate production, while inhibiting photorespiration. By contrast, nitrogen (N) concentrations in leaves generally tend to decline under elevated CO 2 (eCO 2 ), which may reduce the magnitude of photosynthetic enhancement. We tested two hypotheses as to why leaf N is reduced under eCO 2 : (a) A “dilution effect” caused by increased concentration of leaf carbohydrates; and (b) inhibited nitrate assimilation caused by reduced supply of reductant from photorespiration under eCO 2 . This second hypothesis is fully tested in the field for the first time here, using tall trees of a mature Eucalyptus forest exposed to Free‐Air CO 2 Enrichment (EucFACE) for five years. Fully expanded young and mature leaves were both measured for net photosynthesis, photorespiration, total leaf N, nitrate ( ) concentrations, carbohydrates and reductase activity to test these hypotheses. Foliar N concentrations declined by 8% under eCO 2 in new leaves, while the fraction and total carbohydrate concentrations remained unchanged by CO 2 treatment for either new or mature leaves. Photorespiration decreased 31% under eCO 2 supplying less reductant, and in situ reductase activity was concurrently reduced (−34%) in eCO 2 , especially in new leaves during summer periods. Hence, assimilation was inhibited in leaves of E. tereticornis and the evidence did not support a significant dilution effect as a contributor to the observed reductions in leaf N concentration. This finding suggests that the reduction of reductase activity due to lower photorespiration in eCO 2 can contribute to understanding how eCO 2 ‐induced photosynthetic enhancement may be lower than previously expected. We suggest that large‐scale vegetation models simulating effects of eCO 2 on N biogeochemistry include both mechanisms, especially where is major N source to the dominant vegetation and where leaf flushing and emergence occur in temperatures that promote high photorespiration rates.

Climate and soils together regulate photosynthetic carbon isotope discrimination within C 3 plants worldwide - William K. Cornwell; Ian J. Wright; Joel Turner; Vincent Maire; Margaret M. Barbour; Lucas A. Cernusak; Todd Dawson; David Ellsworth; Graham D. Farquhar; Howard Griffiths; Claudia Keitel; Alexander Knohl; et al. (Global Ecology and Biogeography, 2018)
Aim Within C 3 plants, photosynthesis is a balance between CO 2 supply from the atmosphere via stomata and demand by enzymes within chloroplasts. This process is dynamic and a complex but crucial aspect of photosynthesis. We sought to understand the spatial pattern in CO 2 supply–demand balance on a global scale, via analysis of stable isotopes of carbon within leaves (Δ 13 C), which provide an integrative record of CO 2 drawdown during photosynthesis. Location Global Time period 1951–2011. Major taxa studied Vascular plants. Methods We assembled a database of leaf carbon isotope ratios containing 3,979 species–site combinations from across the globe, including 3,645 for C 3 species. We examined a wide array of potential climate and soil drivers of variation in Δ 13 C. Results The strongest drivers of carbon isotope discrimination at the global scale included atmospheric pressure, potential evapotranspiration and soil pH, which explained 44% of the variation in Δ 13 C. Addition of eight more climate and soil variables (each explaining small but highly significant amounts of variation) increased the explained variation to 60%. On top of this, the largest plant trait effect was leaf nitrogen per area, which explained 11% of Δ 13 C variation. Main conclusions: By considering variation in Δ 13 C at a considerably larger scale than previously, we were able to identify and quantify key drivers in CO 2 supply–demand balance previously unacknowledged. Of special note is the key role of soil properties, with greater discrimination on low‐pH and high‐silt soils. Unlike other plant traits, which show typically wide variation within sets of coexisting species, the global pattern in carbon stable isotope ratios is much more conservative; there is relatively narrow variation in time‐integrated CO 2 concentrations at the site of carboxylation among plants in a given soil and climate.

Elevated CO 2 did not affect the hydrological balance of a mature native Eucalyptus woodland - Teresa E. Gimeno; Tim R. McVicar; Anthony P. O'Grady; David T. Tissue; David S. Ellsworth (Global Change Biology, 2018)
Elevated atmospheric CO 2 concentration (e C a ) might reduce forest water‐use, due to decreased transpiration, following partial stomatal closure, thus enhancing water‐use efficiency and productivity at low water availability. If evapotranspiration ( E t ) is reduced, it may subsequently increase soil water storage (Δ S ) or surface runoff ( R ) and drainage ( D g ), although these could be offset or even reversed by changes in vegetation structure, mainly increased leaf area index ( L ). To understand the effect of e C a in a water‐limited ecosystem, we tested whether 2 years of e C a (~40% increase) affected the hydrological partitioning in a mature water‐limited Eucalyptus woodland exposed to Free‐Air CO 2 Enrichment (FACE). This timeframe allowed us to evaluate whether physiological effects of e C a reduced stand water‐use irrespective of L , which was unaffected by e C a in this timeframe. We hypothesized that e C a would reduce tree‐canopy transpiration ( E tree ), but excess water from reduced E tree would be lost via increased soil evaporation and understory transpiration ( E floor ) with no increase in Δ S , R or D g . We computed E t , Δ S , R and D g from measurements of sapflow velocity, L , soil water content (θ), understory micrometeorology, throughfall and stemflow. We found that e C a did not affect E tree , E floor , Δ S or θ at any depth (to 4.5 m) over the experimental period. We closed the water balance for dry seasons with no differences in the partitioning to R and D g between C a levels. Soil temperature and θ were the main drivers of E floor while vapour pressure deficit‐controlled E tree , though e C a did not significantly affect any of these relationships. Our results suggest that in the short‐term, e C a does not significantly affect ecosystem water‐use at this site. We conclude that water‐savings under e C a mediated by either direct effects on plant transpiration or by indirect effects via changes in L or soil moisture availability are unlikely in water‐limited mature eucalypt woodlands.

The Oxygen Paradox, the French Paradox, and age-related diseases - Joanna M. S. Davies; Josiane Cillard; Bertrand Friguet; Enrique Cadenas; Jean Cadet; Rachael Cayce; Andrew Fishmann; David Liao; Anne-Laure Bulteau; Frédéric Derbré; Amélie Rébillard; Steven Burstein; et al. (GeroScience, 2017)

Water availability affects seasonal CO 2 ‐induced photosynthetic enhancement in herbaceous species in a periodically dry woodland - Varsha S. Pathare; Kristine Y. Crous; Julia Cooke; Danielle Creek; Oula Ghannoum; David S. Ellsworth (Global Change Biology, 2017)
Elevated atmospheric CO 2 ( eCO 2 ) is expected to reduce the impacts of drought and increase photosynthetic rates via two key mechanisms: first, through decreased stomatal conductance (g s ) and increased soil water content ( V SWC ) and second, through increased leaf internal CO 2 (C i ) and decreased stomatal limitations (S lim ). It is unclear if such findings from temperate grassland studies similarly pertain to warmer ecosystems with periodic water deficits. We tested these mechanisms in three important C 3 herbaceous species in a periodically dry Eucalyptus woodland and investigated how eCO 2 ‐induced photosynthetic enhancement varied with seasonal water availability, over a 3 year period. Leaf photosynthesis increased by 10%–50% with a 150 μmol mol −1 increase in atmospheric CO 2 across seasons. This eCO 2 ‐induced increase in photosynthesis was a function of seasonal water availability, given by recent precipitation and mean daily V SWC . The highest photosynthetic enhancement by eCO 2 (>30%) was observed during the most water‐limited period, for example, with V SWC eCO 2 there was neither a significant decrease in g s in the three herbaceous species, nor increases in V SWC , indicating no “water‐savings effect” of eCO 2 . Periods of low V SWC showed lower g s (less than ≈ 0.12 mol m −2 s −1 ), higher relative S lim (>30%) and decreased C i under the ambient CO 2 concentration ( aCO 2 ), with leaf photosynthesis strongly carboxylation‐limited. The alleviation of S lim by eCO 2 was facilitated by increasing C i , thus yielding a larger photosynthetic enhancement during dry periods. We demonstrated that water availability, but not eCO 2 , controls g s and hence the magnitude of photosynthetic enhancement in the understory herbaceous plants. Thus, eCO 2 has the potential to alter vegetation functioning in a periodically dry woodland understory through changes in stomatal limitation to photosynthesis, not by the “water‐savings effect” usually invoked in grasslands.

Using models to guide field experiments: a priori predictions for the CO 2 response of a nutrient‐ and water‐limited native Eucalypt woodland - Belinda E. Medlyn; Martin G. De Kauwe; Sönke Zaehle; Anthony P. Walker; Remko A. Duursma; Kristina Luus; Mikhail Mishurov; Bernard Pak; Benjamin Smith; Ying‐Ping Wang; Xiaojuan Yang; Kristine Y. Crous; et al. (Global Change Biology, 2016)
The response of terrestrial ecosystems to rising atmospheric CO 2 concentration (C a ), particularly under nutrient‐limited conditions, is a major uncertainty in Earth System models. The Eucalyptus Free‐Air CO 2 Enrichment (Euc FACE ) experiment, recently established in a nutrient‐ and water‐limited woodland presents a unique opportunity to address this uncertainty, but can best do so if key model uncertainties have been identified in advance. We applied seven vegetation models, which have previously been comprehensively assessed against earlier forest FACE experiments, to simulate a priori possible outcomes from Euc FACE . Our goals were to provide quantitative projections against which to evaluate data as they are collected, and to identify key measurements that should be made in the experiment to allow discrimination among alternative model assumptions in a postexperiment model intercomparison. Simulated responses of annual net primary productivity ( NPP ) to elevated C a ranged from 0.5 to 25% across models. The simulated reduction of NPP during a low‐rainfall year also varied widely, from 24 to 70%. Key processes where assumptions caused disagreement among models included nutrient limitations to growth; feedbacks to nutrient uptake; autotrophic respiration; and the impact of low soil moisture availability on plant processes. Knowledge of the causes of variation among models is now guiding data collection in the experiment, with the expectation that the experimental data can optimally inform future model improvements.

Canopy leaf area of a mature evergreen Eucalyptus woodland does not respond to elevated atmospheric [ CO 2 ] but tracks water availability - Remko A. Duursma; Teresa E. Gimeno; Matthias M. Boer; Kristine Y. Crous; Mark G. Tjoelker; David S. Ellsworth (Global Change Biology, 2016)
Canopy leaf area, quantified by the leaf area index ( L ), is a crucial driver of forest productivity, water use and energy balance. Because L responds to environmental drivers, it can represent an important feedback to climate change, but its responses to rising atmospheric [ CO 2 ] and water availability of forests have been poorly quantified. We studied canopy leaf area dynamics for 28 months in a native evergreen Eucalyptus woodland exposed to free‐air CO 2 enrichment (the Euc FACE experiment), in a subtropical climate where water limitation is common. We hypothesized that, because of expected stimulation of productivity and water‐use efficiency, L should increase with elevated [ CO 2 ]. We estimated L from diffuse canopy transmittance, and measured monthly leaf litter production. Contrary to expectation, L did not respond to elevated [ CO 2 ]. We found that L varied between 1.10 and 2.20 across the study period. The dynamics of L showed a quick increase after heavy rainfall and a steady decrease during periods of low rainfall. Leaf litter production was correlated to changes in L , both during periods of decreasing L (when no leaf growth occurred) and during periods of increasing L (active shedding of old foliage when new leaf growth occurred). Leaf lifespan, estimated from mean L and total annual litter production, was up to 2 months longer under elevated [ CO 2 ] (1.18 vs. 1.01 years; P = 0.05). Our main finding that L was not responsive to elevated CO 2 is consistent with other forest FACE studies, but contrasts with the positive response of L commonly predicted by many ecosystem models.

Short‐term carbon cycling responses of a mature eucalypt woodland to gradual stepwise enrichment of atmospheric CO 2 concentration - John E. Drake; Catriona A. Macdonald; Mark G. Tjoelker; Kristine Y. Crous; Teresa E. Gimeno; Brajesh K. Singh; Peter B. Reich; Ian C. Anderson; David S. Ellsworth (Global Change Biology, 2016)
Projections of future climate are highly sensitive to uncertainties regarding carbon (C) uptake and storage by terrestrial ecosystems. The Eucalyptus Free‐Air CO 2 Enrichment (Euc FACE ) experiment was established to study the effects of elevated atmospheric CO 2 concentrations (eCO 2 ) on a native mature eucalypt woodland with low fertility soils in southeast Australia. In contrast to other FACE experiments, the concentration of CO 2 at Euc FACE was increased gradually in steps above ambient (+0, 30, 60, 90, 120, and 150 ppm CO 2 above ambient of ~400 ppm), with each step lasting approximately 5 weeks. This provided a unique opportunity to study the short‐term (weeks to months) response of C cycle flux components to eCO 2 across a range of CO 2 concentrations in an intact ecosystem. Soil CO 2 efflux (i.e., soil respiration or R soil ) increased in response to initial enrichment (e.g., +30 and +60 ppm CO 2 ) but did not continue to increase as the CO 2 enrichment was stepped up to higher concentrations. Light‐saturated photosynthesis of canopy leaves ( A sat ) also showed similar stimulation by elevated CO 2 at +60 ppm as at +150 ppm CO 2 . The lack of significant effects of eCO 2 on soil moisture, microbial biomass, or activity suggests that the increase in R soil likely reflected increased root and rhizosphere respiration rather than increased microbial decomposition of soil organic matter. This rapid increase in R soil suggests that under eCO 2, additional photosynthate was produced, transported belowground, and respired. The consequences of this increased belowground activity and whether it is sustained through time in mature ecosystems under eCO 2 are a priority for future research.

Response of belowground communities to short-term phosphorus addition in a phosphorus-limited woodland - Uffe N. Nielsen; Samantha Prior; Brendan Delroy; Jennifer K. M. Walker; David S. Ellsworth; Jeff R. Powell (Plant and Soil, 2015)

Global effects of soil and climate on leaf photosynthetic traits and rates - Vincent Maire; Ian J. Wright; I. Colin Prentice; Niels H. Batjes; Radika Bhaskar; Peter M. van Bodegom; Will K. Cornwell; David Ellsworth; Ülo Niinemets; Alejandro Ordonez; Peter B. Reich; Louis S. Santiago (Global Ecology and Biogeography, 2015)
Aim The influence of soil properties on photosynthetic traits in higher plants is poorly quantified in comparison with that of climate. We address this situation by quantifying the unique and joint contributions to global leaf‐trait variation from soils and climate. Location Terrestrial ecosystems world‐wide. Methods Using a trait dataset comprising 1509 species from 288 sites, with climate and soil data derived from global datasets, we quantified the effects of 20 soil and 26 climate variables on light‐saturated photosynthetic rate ( A area ), stomatal conductance ( g s ), leaf nitrogen and phosphorus ( N area and P area ) and specific leaf area ( SLA ) using mixed regression models and multivariate analyses. Results Soil variables were stronger predictors of leaf traits than climatic variables, except for SLA . On average, N area , P area and A area increased and SLA decreased with increasing soil pH and with increasing site aridity. g s declined and P area increased with soil available P ( P avail ). N area was unrelated to total soil N . Joint effects of soil and climate dominated over their unique effects on N area and P area , while unique effects of soils dominated for A area and g s . Path analysis indicated that variation in A area reflected the combined independent influences of N area and g s , the former promoted by high pH and aridity and the latter by low P avail . Main conclusions Three environmental variables were key for explaining variation in leaf traits: soil pH and P avail , and the climatic moisture index (the ratio of precipitation to potential evapotranspiration). Although the reliability of global soil datasets lags behind that of climate datasets, our results nonetheless provide compelling evidence that both can be jointly used in broad‐scale analyses, and that effects uniquely attributable to soil properties are important determinants of leaf photosynthetic traits and rates. A significant future challenge is to better disentangle the covarying physiological, ecological and evolutionary mechanisms that underpin trait–environment relationships.

Photosynthesis of temperate E ucalyptus globulus trees outside their native range has limited adjustment to elevated CO 2 and climate warming - Kristine Y. Crous; Audrey G. Quentin; Yan‐Shih Lin; Belinda E. Medlyn; David G. Williams; Craig V. M. Barton; David S. Ellsworth (Global Change Biology, 2013)
E ucalyptus species are grown widely outside of their native ranges in plantations on all vegetated continents of the world. We predicted that such a plantation species would show high potential for acclimation of photosynthetic traits across a wide range of growth conditions, including elevated [ CO 2 ] and climate warming. To test this prediction, we planted temperate E ucalyptus globulus Labill. seedlings in climate‐controlled chambers in the field located >700 km closer to the equator than the nearest natural occurrence of this species. Trees were grown in a complete factorial combination of elevated CO 2 concentration ( eC ; ambient [ CO 2 ] +240 ppm) and air warming treatments ( eT ; ambient +3 °C) for 15 months until they reached ca. 10 m height. There was little acclimation of photosynthetic capacity to eC and hence the CO 2 ‐induced photosynthetic enhancement was large (ca. 50%) in this treatment during summer. The warming treatment significantly increased rates of both carboxylation capacity ( V cmax ) and electron transport ( J max ) (measured at a common temperature of 25 °C) during winter, but decreased them significantly by 20–30% in summer. The photosynthetic CO 2 compensation point in the absence of dark respiration ( Γ *) was relatively less sensitive to temperature in this temperate eucalypt species than for warm‐season tobacco. The temperature optima for photosynthesis and J max significantly changed by about 6 °C between winter and summer, but without further adjustment from early to late summer. These results suggest that there is an upper limit for the photosynthetic capacity of E . globulus ssp. globulus outside its native range to acclimate to growth temperatures above 25 °C. Limitations to temperature acclimation of photosynthesis in summer may be one factor that defines climate zones where E . globulus plantation productivity can be sustained under anticipated global environmental change.

Forest water use and water use efficiency at elevated CO 2 : a model‐data intercomparison at two contrasting temperate forest FACE sites - Martin G. De Kauwe; Belinda E. Medlyn; Sönke Zaehle; Anthony P. Walker; Michael C. Dietze; Thomas Hickler; Atul K. Jain; Yiqi Luo; William J. Parton; I. Colin Prentice; Benjamin Smith; Peter E. Thornton; et al. (Global Change Biology, 2013)
Predicted responses of transpiration to elevated atmospheric CO 2 concentration ( eCO 2 ) are highly variable amongst process‐based models. To better understand and constrain this variability amongst models, we conducted an intercomparison of 11 ecosystem models applied to data from two forest free‐air CO 2 enrichment ( FACE ) experiments at Duke University and Oak Ridge National Laboratory. We analysed model structures to identify the key underlying assumptions causing differences in model predictions of transpiration and canopy water use efficiency. We then compared the models against data to identify model assumptions that are incorrect or are large sources of uncertainty. We found that model‐to‐model and model‐to‐observations differences resulted from four key sets of assumptions, namely (i) the nature of the stomatal response to elevated CO 2 (coupling between photosynthesis and stomata was supported by the data); (ii) the roles of the leaf and atmospheric boundary layer (models which assumed multiple conductance terms in series predicted more decoupled fluxes than observed at the broadleaf site); (iii) the treatment of canopy interception (large intermodel variability, 2–15%); and (iv) the impact of soil moisture stress (process uncertainty in how models limit carbon and water fluxes during moisture stress). Overall, model predictions of the CO 2 effect on WUE were reasonable (intermodel μ = approximately 28% ± 10%) compared to the observations (μ = approximately 30% ± 13%) at the well‐coupled coniferous site (Duke), but poor (intermodel μ = approximately 24% ± 6%; observations μ = approximately 38% ± 7%) at the broadleaf site (Oak Ridge). The study yields a framework for analysing and interpreting model predictions of transpiration responses to eCO 2 , and highlights key improvements to these types of models.

Reconciling the optimal and empirical approaches to modelling stomatal conductance - Belinda E. Medlyn; Remko A. Duursma; Derek Eamus; David S. Ellsworth; I. Colin Prentice; Craig V. M. Barton; Kristine Y. Crous; Paolo de Angelis; Michael Freeman; Lisa Wingate (Global Change Biology, 2012)

Effects of elevated atmospheric [ CO 2 ] on instantaneous transpiration efficiency at leaf and canopy scales in E ucalyptus saligna - Craig V.M. Barton; Remko A. Duursma; Belinda E. Medlyn; David S. Ellsworth; Derek Eamus; David T. Tissue; Mark A. Adams; Jann Conroy; Kristine Y. Crous; Marion Liberloo; Markus Löw; Sune Linder; et al. (Global Change Biology, 2012)
Rising atmospheric concentrations of CO 2 ( C a ) can reduce stomatal conductance and transpiration rate in trees, but the magnitude of this effect varies considerably among experiments. The theory of optimal stomatal behaviour predicts that the ratio of photosynthesis to transpiration (instantaneous transpiration efficiency, ITE ) should increase in proportion to C a . We hypothesized that plants regulate stomatal conductance optimally in response to rising C a . We tested this hypothesis with data from young Eucalyptus saligna Sm. trees grown in 12 climate‐controlled whole‐tree chambers for 2 years at ambient and elevated C a . Elevated C a was ambient + 240 ppm, 60% higher than ambient C a . Leaf‐scale gas exchange was measured throughout the second year of the study and leaf‐scale ITE increased by 60% under elevated C a , as predicted. Values of leaf‐scale ITE depended strongly on vapour pressure deficit ( D ) in both CO 2 treatments. Whole‐canopy CO 2 and H 2 O fluxes were also monitored continuously for each chamber throughout the second year. There were small differences in D between C a treatments, which had important effects on values of canopy‐scale ITE . However, when C a treatments were compared at the same D , canopy‐scale ITE was consistently increased by 60%, again as predicted. Importantly, leaf and canopy‐scale ITE were not significantly different, indicating that ITE was not scale‐dependent. Observed changes in transpiration rate could be explained on the basis that ITE increased in proportion to C a . The effect of elevated C a on photosynthesis increased with rising D . At high D , C a had a large effect on photosynthesis and a small effect on transpiration rate. At low D , in contrast, there was a small effect of C a on photosynthesis, but a much larger effect on transpiration rate. If shown to be a general response, the proportionality of ITE with C a will allow us to predict the effects of C a on transpiration rate.

Elevated CO 2 affects photosynthetic responses in canopy pine and subcanopy deciduous trees over 10 years: a synthesis from D uke FACE - David S. Ellsworth; Richard Thomas; Kristine Y. Crous; Sari Palmroth; Eric Ward; Chris Maier; Evan DeLucia; Ram Oren (Global Change Biology, 2012)
Leaf responses to elevated atmospheric CO 2 concentration (C a ) are central to models of forest CO 2 exchange with the atmosphere and constrain the magnitude of the future carbon sink. Estimating the magnitude of primary productivity enhancement of forests in elevated C a requires an understanding of how photosynthesis is regulated by diffusional and biochemical components and up‐scaled to entire canopies. To test the sensitivity of leaf photosynthesis and stomatal conductance to elevated C a in time and space, we compiled a comprehensive dataset measured over 10 years for a temperate pine forest of P inus taeda , but also including deciduous species, primarily L iquidambar styraciflua . We combined over one thousand controlled‐response curves of photosynthesis as a function of environmental drivers (light, air C a and temperature) measured at canopy heights up to 20 m over 11 years (1996–2006) to generate parameterizations for leaf‐scale models for the D uke free‐air CO 2 enrichment ( FACE ) experiment. The enhancement of leaf net photosynthesis ( A net ) in P . taeda by elevated C a of +200 μmol mol −1 was 67% for current‐year needles in the upper crown in summer conditions over 10 years. Photosynthetic enhancement of P . taeda at the leaf‐scale increased by two‐fold from the driest to wettest growing seasons. Current‐year pine foliage A net was sensitive to temporal variation, whereas previous‐year foliage A net was less responsive and overall showed less enhancement (+30%). Photosynthetic downregulation in overwintering upper canopy pine needles was small at average leaf N ( N area ), but statistically significant. In contrast, co‐dominant and subcanopy L . styraciflua trees showed A net enhancement of 62% and no A net – N area adjustments. Various understory deciduous tree species showed an average A net enhancement of 42%. Differences in photosynthetic responses between overwintering pine needles and subcanopy deciduous leaves suggest that increased C a has the potential to enhance the mixed‐species composition of planted pine stands and, by extension, naturally regenerating pine‐dominated stands.

Forest Canopy Properties and Variation in Aboveground Net Primary Production over Upper Great Lakes Landscapes - Iryna Dronova; Kathleen M. Bergen; David S. Ellsworth (Ecosystems, 2011)

Maintenance of leaf N controls the photosynthetic CO 2 response of grassland species exposed to 9 years of free‐air CO 2 enrichment - KRISTINE Y. CROUS; PETER B. REICH; MARK D. HUNTER; DAVID S. ELLSWORTH (Global Change Biology, 2010)
Determining underlying physiological patterns governing plant productivity and diversity in grasslands are critical to evaluate species responses to future environmental conditions of elevated CO 2 and nitrogen (N) deposition. In a 9‐year experiment, N was added to monocultures of seven C 3 grassland species exposed to elevated atmospheric CO 2 (560 μmol CO 2 mol −1 ) to evaluate how N addition affects CO 2 responsiveness in species of contrasting functional groups. Functional groups differed in their responses to elevated CO 2 and N treatments. Forb species exhibited strong down‐regulation of leaf N mass concentrations (−26%) and photosynthetic capacity (−28%) in response to elevated CO 2 , especially at high N supply, whereas C 3 grasses did not. Hence, achieved photosynthetic performance was markedly enhanced for C 3 grasses (+68%) in elevated CO 2 , but not significantly for forbs. Differences in access to soil resources between forbs and grasses may distinguish their responses to elevated CO 2 and N addition. Forbs had lesser root biomass, a lower distribution of biomass to roots, and lower specific root length than grasses. Maintenance of leaf N, possibly through increased root foraging in this nutrient‐poor grassland, was necessary to sustain stimulation of photosynthesis under long‐term elevated CO 2 . Dilution of leaf N and associated photosynthetic down‐regulation in forbs under elevated [CO 2 ], relative to the C 3 grasses, illustrates the potential for shifts in species composition and diversity in grassland ecosystems that have significant forb and grass components.

Forest fine‐root production and nitrogen use under elevated CO 2 : contrasting responses in evergreen and deciduous trees explained by a common principle - OSKAR FRANKLIN; ROSS E. McMURTRIE; COLLEEN M. IVERSEN; KRISTINE Y. CROUS; ADRIEN C. FINZI; DAVID T. TISSUE; DAVID S. ELLSWORTH; RAM OREN; RICHARD J. NORBY (Global Change Biology, 2009)
Despite the importance of nitrogen (N) limitation of forest carbon (C) sequestration at rising atmospheric CO 2 concentration, the mechanisms responsible are not well understood. To elucidate the interactive effects of elevated CO 2 (eCO 2 ) and soil N availability on forest productivity and C allocation, we hypothesized that (1) trees maximize fitness by allocating N and C to maximize their net growth and (2) that N uptake is controlled by soil N availability and root exploration for soil N. We tested this model using data collected in Free‐Air CO 2 Enrichment sites dominated by evergreen ( Pinus taeda ; Duke Forest) and deciduous [ Liquidambar styraciflua ; Oak Ridge National Laboratory (ORNL)] trees. The model explained 80–95% of variation in productivity and N‐uptake data among eCO 2 , N fertilization and control treatments over 6 years. The model explains why fine‐root production increased, and why N uptake increased despite reduced soil N availability under eCO 2 at ORNL and Duke. In agreement with observations at other sites, the model predicts that soil N availability reduced below a critical level diminishes all eCO 2 responses. At Duke, a negative feedback between reduced soil N availability and N uptake prevented progressive reduction in soil N availability at eCO 2 . At ORNL, soil N availability progressively decreased because it did not trigger reductions in N uptake; N uptake was maintained at ORNL through a large increase in the production of fast turnover fine roots. This implies that species with fast root turnover could be more prone to progressive N limitation of carbon sequestration in woody biomass than species with slow root turnover, such as evergreens. However, longer term data are necessary for a thorough evaluation of this hypothesis. The success of the model suggests that the principle of maximization of net growth to control growth and allocation could serve as a basis for simplification and generalization of larger scale forest and ecosystem models, for example by removing the need to specify parameters for relative foliage/stem/root allocation.

Temporal dynamics and spatial variability in the enhancement of canopy leaf area under elevated atmospheric CO 2 - HEATHER R. McCARTHY; RAM OREN; ADRIEN C. FINZI; DAVID S. ELLSWORTH; HYUN‐SEOK KIM; KURT H. JOHNSEN; BONNIE MILLAR (Global Change Biology, 2007)
Increased canopy leaf area ( L ) may lead to higher forest productivity and alter processes such as species dynamics and ecosystem mass and energy fluxes. Few CO 2 enrichment studies have been conducted in closed canopy forests and none have shown a sustained enhancement of L . We reconstructed 8 years (1996–2003) of L at Duke's Free Air CO 2 Enrichment experiment to determine the effects of elevated atmospheric CO 2 concentration ([CO 2 ]) on L before and after canopy closure in a pine forest with a hardwood component, focusing on interactions with temporal variation in water availability and spatial variation in nitrogen (N) supply. The dynamics of L were reconstructed using data on leaf litterfall mass and specific leaf area for hardwoods, and needle litterfall mass and specific leaf area combined with needle elongation rates, and fascicle and shoot counts for pines. The dynamics of pine L production and senescence were unaffected by elevated [CO 2 ], although L senescence for hardwoods was slowed. Elevated [CO 2 ] enhanced pine L and the total canopy L (combined pine and hardwood species; P L and its response to elevated [CO 2 ] was not random. Each year pine L under ambient and elevated [CO 2 ] was spatially correlated to the variability in site nitrogen availability (e.g. r 2 =0.94 and 0.87 in 2001, when L was highest before declining due to droughts and storms), with the [CO 2 ]‐induced enhancement increasing with N ( P =0.061). Incorporating data on N beyond the range of native fertility, achieved through N fertilization, indicated that pine L had reached the site maximum under elevated [CO 2 ] where native N was highest. Thus closed canopy pine forests may be able to increase leaf area under elevated [CO 2 ] in moderate fertility sites, but are unable to respond to [CO 2 ] in both infertile sites (insufficient resources) and sites having high levels of fertility (maximum utilization of resources). The total canopy L , representing the combined L of pine and hardwood species, was constant across the N gradient under both ambient and elevated [CO 2 ], generating a constant enhancement of canopy L . Thus, in mixed species stands, L of canopy hardwoods which developed on lower fertility sites (∼3 g N inputs m −2 yr −1 ) may be sufficiently enhanced under elevated [CO 2 ] to compensate for the lack of response in pine L , and generate an appreciable response of total canopy L (∼14%).

Belowground competition and the response of developing forest communities to atmospheric CO 2 and O 3 - DONALD R. ZAK; WILLIAM E. HOLMES; KURT S. PREGITZER; JOHN S. KING; DAVID S. ELLSWORTH; MARK E. KUBISKE (Global Change Biology, 2007)
As human activity continues to increase CO 2 and O 3 , broad expanses of north temperate forests will be simultaneously exposed to elevated concentrations of these trace gases. Although both CO 2 and O 3 are potent modifiers of plant growth, we do not understand the extent to which they alter competition for limiting soil nutrients, like nitrogen (N). We quantified the acquisition of soil N in two 8‐year‐old communities composed of trembling aspen genotypes ( n = 5) and trembling aspen–paper birch which were exposed to factorial combinations of CO 2 (ambient and 560 μL L −1 ) and O 3 (ambient = 30–40 vs. 50–60 nL L −1 ). Tracer amount of 15 NH 4 + were applied to soil to determine how these trace gases altered the competitive ability of genotypes and species to acquire soil N. One year after isotope addition, we assessed N acquisition by measuring the amount of 15 N tracer contained in the plant canopy (i.e. recent N acquisition), as well as the total amount of canopy N (i.e. cumulative N acquisition). Exposure to elevated CO 2 differentially altered recent and cumulative N acquisition among aspen genotypes, changing the rank order in which they obtained soil N. Elevated O 3 also altered the rank order in which aspen genotypes obtained soil N by eliciting increases, decreases and no response among genotypes. If aspen genotypes respond similarly under field conditions, then rising concentrations of CO 2 and O 3 could alter the structure of aspen populations. In the aspen–birch community, elevated CO 2 increased recent N (i.e. 15 N) acquisition in birch (68%) to a greater extent than aspen (19%), suggesting that, over the course of this experiment, birch had gained a competitive advantage over aspen. The response of genotypes and species to rising CO 2 and O 3 concentrations, and how these responses are modified by competitive interactions, has the potential to change the future composition and productivity of northern temperate forests.

Plant species richness, elevated CO 2 , and atmospheric nitrogen deposition alter soil microbial community composition and function - HAEGEUN CHUNG; DONALD R. ZAK; PETER B. REICH; DAVID S. ELLSWORTH (Global Change Biology, 2007)
We determined soil microbial community composition and function in a field experiment in which plant communities of increasing species richness were exposed to factorial elevated CO 2 and nitrogen (N) deposition treatments. Because elevated CO 2 and N deposition increased plant productivity to a greater extent in more diverse plant assemblages, it is plausible that heterotrophic microbial communities would experience greater substrate availability, potentially increasing microbial activity, and accelerating soil carbon (C) and N cycling. We, therefore, hypothesized that the response of microbial communities to elevated CO 2 and N deposition is contingent on the species richness of plant communities. Microbial community composition was determined by phospholipid fatty acid analysis, and function was measured using the activity of key extracellular enzymes involved in litter decomposition. Higher plant species richness, as a main effect, fostered greater microbial biomass, cellulolytic and chitinolytic capacity, as well as the abundance of saprophytic and arbuscular mycorrhizal (AM) fungi. Moreover, the effect of plant species richness on microbial communities was significantly modified by elevated CO 2 and N deposition. For instance, microbial biomass and fungal abundance increased with greater species richness, but only under combinations of elevated CO 2 and ambient N, or ambient CO 2 and N deposition. Cellobiohydrolase activity increased with higher plant species richness, and this trend was amplified by elevated CO 2 . In most cases, the effect of plant species richness remained significant even after accounting for the influence of plant biomass. Taken together, our results demonstrate that plant species richness can directly regulate microbial activity and community composition, and that plant species richness is a significant determinant of microbial response to elevated CO 2 and N deposition. The strong positive effect of plant species richness on cellulolytic capacity and microbial biomass indicate that the rates of soil C cycling may decline with decreasing plant species richness.

Plant species richness, elevated CO 2 , and atmospheric nitrogen deposition alter soil microbial community composition and function - HAEGEUN CHUNG; DONALD R. ZAK; PETER B. REICH; DAVID S. ELLSWORTH (Global Change Biology, 2007)

Seedling survival in a northern temperate forest understory is increased by elevated atmospheric carbon dioxide and atmospheric nitrogen deposition - LESLEY T. SEFCIK; DONALD R. ZAK; DAVID S. ELLSWORTH (Global Change Biology, 2007)
We tested the main and interactive effects of elevated carbon dioxide concentration ([CO 2 ]), nitrogen (N), and light availability on leaf photosynthesis, and plant growth and survival in understory seedlings grown in an N‐limited northern hardwood forest. For two growing seasons, we exposed six species of tree seedlings ( Betula papyrifera, Populus tremuloides, Acer saccharum , Fagus grandifolia , Pinus strobus , and Prunus serotina ) to a factorial combination of atmospheric CO 2 (ambient, and elevated CO 2 at 658 μmol CO 2 mol −1 ) and N deposition (ambient and ambient +30 kg N ha −1 yr −1 ) in open‐top chambers placed in an understory light gradient. Elevated CO 2 exposure significantly increased apparent quantum efficiency of electron transport by 41% ( P P P 2 ]. Experimental N deposition significantly increased light‐limited photosynthesis as light availability increased ( P P 2 exposure and high N availability did not affect seedling growth; however, growth increased slightly with light availability ( R 2 =0.26, P P 2 ] and N deposition ( P R 2 =0.39, P V cmax ) was a better predictor for seedling growth and survival than maximum photosynthetic rate ( A max ). Our results suggest that increasing [CO 2 ] and N deposition from fossil fuel combustion could alter understory tree species recruitment dynamics through changes in seedling survival, and this has the potential to alter future forest species composition.

Photosynthesis, carboxylation and leaf nitrogen responses of 16 species to elevated pCO 2 across four free‐air CO 2 enrichment experiments in forest, grassland and desert - David S. Ellsworth; Peter B. Reich; Elke S. Naumburg; George W. Koch; Mark E. Kubiske; Stan D. Smith (Global Change Biology, 2004)
The magnitude of changes in carboxylation capacity in dominant plant species under long‐term elevated CO 2 exposure (elevated pC a ) directly impacts ecosystem CO 2 assimilation from the atmosphere. We analyzed field CO 2 response curves of 16 C 3 species of different plant growth forms in favorable growth conditions in four free‐air CO 2 enrichment (FACE) experiments in a pine and deciduous forest, a grassland and a desert. Among species and across herb, tree and shrub growth forms there were significant enhancements in CO 2 assimilation ( A ) by +40±5% in elevated pC a (49.5–57.1 Pa), although there were also significant reductions in photosynthetic capacity in elevated pC a in some species. Photosynthesis at a common pC a ( A a ) was significantly reduced in five species growing under elevated pC a , while leaf carboxylation capacity ( V cmax ) was significantly reduced by elevated pC a in seven species (change of −19±3% among these species) across different growth forms and FACE sites. Adjustments in V cmax with elevated pC a were associated with changes in leaf N among species, and occurred in species with the highest leaf N. Elevated pC a treatment did not affect the mass‐based relationships between A or V cmax and N, which differed among herbs, trees and shrubs. Thus, effects of elevated pC a on leaf C assimilation and carboxylation capacity occurred largely through changes in leaf N, rather than through elevated pC a effects on the relationships themselves. Maintenance of leaf carboxylation capacity among species in elevated pC a at these sites depends on maintenance of canopy N stocks, with leaf N depletion associated with photosynthetic capacity adjustments. Since CO 2 responses can only be measured experimentally on a small number of species, understanding elevated CO 2 effects on canopy N m and N a will greatly contribute to an ability to model responses of leaf photosynthesis to atmospheric CO 2 in different species and plant growth forms.

Exposure to an enriched CO 2 atmosphere alters carbon assimilation and allocation in a pine forest ecosystem - Karina V. R. Schäfer; Ram Oren; David S. Ellsworth; Chun‐Ta Lai; Jeffrey D. Herrick; Adrien C. Finzi; Daniel D. Richter; Gabriel G. Katul (Global Change Biology, 2003)
We linked a leaf‐level CO 2 assimilation model with a model that accounts for light attenuation in the canopy and measurements of sap‐flux‐based canopy conductance into a new canopy conductance‐constrained carbon assimilation (4C‐A) model. We estimated canopy CO 2 uptake ( A nC ) at the Duke Forest free‐air CO 2 enrichment (FACE) study. Rates of A nC estimated from the 4C‐A model agreed well with leaf gas exchange measurements ( A net ) in both CO 2 treatments. Under ambient conditions, monthly sums of net CO 2 uptake by the canopy ( A nC ) were 13% higher than estimates based on eddy‐covariance and chamber measurements. Annual estimates of A nC were only 3% higher than carbon (C) accumulations and losses estimated from ground‐based measurements for the entire stand. The C budget for the Pinus taeda component was well constrained (within 1% of ground‐based measurements). Although the closure of the C budget for the broadleaf species was poorer (within 20%), these species are a minor component of the forest. Under elevated CO 2 , the C used annually for growth, turnover, and respiration balanced only 80% of the A nC . Of the extra 700 g C m −2 a −1 (1999 and 2000 average), 86% is attributable to surface soil CO 2 efflux. This suggests that the production and turnover of fine roots was underestimated or that mycorrhizae and rhizodeposition became an increasingly important component of the C balance. Under elevated CO 2 , net ecosystem production increased by 272 g C m −2 a −1 : 44% greater than under ambient CO 2 . The majority (87%) of this C was sequestered in a moderately long‐term C pool in wood, with the remainder in the forest floor–soil subsystem.

Modeling dynamic understory photosynthesis of contrasting species in ambient and elevated carbon dioxide - Elke Naumburg; David S. Ellsworth; Gabriel G. Katul (Oecologia, 2001)

Elevated Carbon Dioxide in the Atmosphere: What Might It Mean for Loblolly Pine Plantation Forestry? - John W. Groninger; Kurt H. Johnsen; John R. Seiler; Rodney E. Will; David S. Ellsworth; Chris A. Maier (Journal of Forestry, 1999)
Research with Loblolly pine suggests that projected increases in atmospheric CO2 concentration will accelerate early growth and could result in shorter rotation length, reduced time until first commercial thinning, higher optimal planting density, and possibly higher maximum stocking level in managed stands. We discuss some of the physiological processes and stand dynamics that underlie these changes, as well as silvicultural strategies that may serve to ensure sustainability of intensively managed forest systems in the face of increasing CO2 and possible climate change.

A free‐air enrichment system for exposing tall forest vegetation to elevated atmospheric CO 2 - George R. Hendrey; David S. Ellsworth; Keith F. Lewin; JohN. Nagy (Global Change Biology, 1999)
A free‐air CO 2 enrichment (FACE) system was designed to permit the experimental exposure of tall vegetation such as stands of forest trees to elevated atmospheric CO 2 concentrations ([CO 2 ] a ) without enclosures that alter tree microenvironment. We describe a prototype FACE system currently in operation in forest plots in a maturing loblolly pine ( Pinus taeda L.) stand in North Carolina, USA. The system uses feedback control technology to control [CO 2 ] in a 26 m diameter forest plot that is over 10 m tall, while monitoring the 3D plot volume to characterize the whole‐stand CO 2 regime achieved during enrichment. In the second summer season of operation of the FACE system, atmospheric CO 2 enrichment was conducted in the forest during all daylight hours for 96.7% of the scheduled running time from 23 May to 14 October with a preset target [CO 2 ] of 550 μmol mol –1 , ≈ 200 μmol mol –1 above ambient [CO 2 ]. The system provided spatial and temporal control of [CO 2 ] similar to that reported for open‐top chambers over trees, but without enclosing the vegetation. The daily average daytime [CO 2 ] within the upper forest canopy at the centre of the FACE plot was 552 ± 9 μmol mol –1 (mean ± SD). The FACE system maintained 1‐minute average [CO 2 ] to within ± 110 μmol mol –1 of the target [CO 2 ] for 92% of the operating time. Deviations of [CO 2 ] outside of this range were short‐lived (most lasting 2 ] by the system was achieved, with over 90% of the entire canopy volume within ± 10% of the target [CO 2 ] over the exposure season. CO 2 consumption by the FACE system was much higher than for open‐top chambers on an absolute basis, but similar to that of open‐top chambers and branch bag chambers on a per unit volume basis. CO 2 consumption by the FACE system was strongly related to windspeed, averaging 50 g CO 2 m –3 h –1 for the stand for an average windspeed of 1.5 m s –1 during summer. The [CO 2 ] control results show that the free‐air approach is a tractable way to study long‐term and short‐term alterations in trace gases, even within entire tall forest ecosystems. The FACE approach permits the study of a wide range of forest stand and ecosystem processes under manipulated [CO 2 ] a that were previously impossible or intractable to study in true forest ecosystems.

Relationships of leaf dark respiration to leaf nitrogen, specific leaf area and leaf life-span: a test across biomes and functional groups - Peter B. Reich; Michael B. Walters; David S. Ellsworth; James M. Vose; John C. Volin; Charles Gresham; William D. Bowman (Oecologia, 1998)